The study of transformed herbaceous vegetation in the area flooded due to coal mine workings - Lykholat, Yuriy; Лихолат, Юрій; Khromykh, Nina; Хромих, Ніна; Didur, Oleh; Дідур, Олег; Kotovych, Oleksandr; Котович, Олександр; Kovalenko, Igor; Коваленко, Ігор; Kovalenko, Vladyslav; Коваленко, Владислав; et al. (Institute of Landscape Ecology of Slovak Academy of Sciences, 2021)
The spontaneous vegetation in permanent flooding zone around technogenic water bodies arising on former pastures due to underground coal min-ing in the Western Donbass basin (steppe zone of Ukraine) was studied in 2018–2019. Occurrence and abundance of herbaceous plants were taken into account in 36 vegetation plots over a total area of 0.8 km2 in different habitats: dry, wet and flooded. In total, 83 plant species belonging to 31 families and 66 genera were identified, among which perennials dominated. Strong negative Pearson’s correlation was found between the amount and abundance of plant species and soil characteristics across the studied habitats, where the joint action of all edaphic factors determined the mosaic appearance of transformed vegetation. The spontaneous vegetation of the least disturbed xero-mesophilic habitats was most similar to (semi)natural grasslands, while the vegetation of hygrophilic habitats had a complete mismatch. Surrounding grasslands were not the most important diasporas’ source for spontaneous succession in the disturbed zone, and many species were supposed to come from the more remote areas. Recovery of target vegetation did not occur for 25 years of permanent subsidence and flooding due to radical transformation of landscape and soil and appearance of completely inappropriate habitats. At the same time, the unusual species composition of spontaneous vegetation and significant number of rare and endangered plants indicate the formation of valuable biotopes in the subsidence and flooding zone. У 2018–2019 рр. досліджували стихійну рослинність у зоні постійного затоплення навколо техногенних водойм, що виникають на колишніх пасовищах внаслідок підземного видобутку вугілля в басейні Західного Донбасу (степова зона України). Враховано поширеність та чисельність трав’янистих рослин на 36 ділянках рослинності загальною площею 0,8 км² у різних біотопах: сухих, вологих та затоплених. Всього виявлено 83 види рослин, що належать до 31 родини та 66 родів, серед яких домінували багаторічники. Виявлено сильний негативний кореляційний зв’язок Пірсона між кількістю та чисельністю видів рослин і характеристиками ґрунтів у досліджуваних біотопах, де спільна дія всіх едафічних факторів визначала мозаїчний вигляд трансформованої рослинності. Спонтанна рослинність найменш порушених ксеромезофільних біотопів була найбільш схожою на напівприродні луки, тоді як рослинність гігрофільних біотопів мала повну невідповідність. Навколишні луки не були найважливішим джерелом діаспор для спонтанної сукцесії в порушеній зоні, і багато видів мали б поширитися з більш віддалених районів. Відновлення цільової рослинності не відбулося за 25 років постійного осідання та підтоплення через радикальну трансформацію ландшафту, ґрунту та появу абсолютно невідповідних біотопів. Водночас незвичайний видовий склад спонтанної рослинності та значна кількість рідкісних та зникаючих рослин свідчать про формування цінних біотопів у зоні просідання та затоплення.
Вивчення трансформованої трав'янистої рослинності на території, що підтоплена внаслідок вугільних виробок
Keywords: herbaceous plants; трав’янисті рослини; flooding; затоплення; succession; сукцесія; target vegetation; цільова рослинність; habitat types; типи середовища існування